The Argentine radioactive waste repository. Basic criteria, preliminary siting and desing conceptual basis - Beninson, Dan Jacobo; González, Abel Julio; Palacios, Elías; Ciallella, Norberto R. (International Atomic Energy Agency, Viena; Austria, 1986)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina